IoT-Based Water Quality Monitoring System for Koi Fish Quarantine - Andiyansyah, Rizki Novan; Setyawati, Onny; Hario Partiansyah, Fakhriy (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2024)
Koi fish have a prominent attraction with their uniqueness including their beautiful shape, color, and pattern, making Koi fish very popular among ornamental fish. Koi fish undergo a quarantine process before being placed in the cultivation pond. The quarantine process is necessary because Koi fish are taken from paddy field ponds, where diseases from the external environment, such as fungi, bacteria, and parasites, may still be present. This research involves four parameters that support good water quality for the life and growth of Koi fish: temperature, acidity level (pH), Total Dissolved Solid (TDS), and water turbidity. This research aims to monitor the quality of Koi fish quarantine using the four parameters above using the Internet of Things (IoT). Water quality measurement data from these four sensors can be detected in real-time via the Internet of Things (IoT) using the Blynk application as a monitoring tool and the Telegram application as a notification to Telegram if the water quality is not ideal.